Loading dose and efficacy of continuous or extended infusion of beta‐lactams compared with intermittent administration in patients with critical illnesses: A subgroup meta‐analysis and meta‐regression analysis - Wu, Chih‐Chien; Su, Yi‐Chia; Wu, Kuan‐Sheng; Wu, Tung‐Ho; Yang, Ching‐Shiang (Journal of clinical pharmacy and therapeutics, 2021)
What is known and objective The role of continuous/extended beta‐lactam infusions (CEIs) in improving clinical outcomes among critically ill patients remains controversial. Therefore, we aimed to compare the clinical efficacy of CEI versus intermittent administration (IA) of beta‐lactams by performing a systematic review and meta‐analysis. Methods PubMed, the Cochrane Library and Embase were searched from inception until December 2018 for studies comparing clinical outcomes of CEI versus IA in critically ill patients. The meta‐analysis included 18 randomized controlled trials (RCTs) and 13 non‐RCTs. Results and discussion For CEI versus IA, the summary relative risk (RR) for overall mortality and clinical cure was 0.82 (95% confidence interval [CI]: 0.72–0.94) and 1.31 (95% CI: 1.15–1.49), respectively. Subgroup and meta‐regression analyses of the loading dose revealed a significantly increased clinical cure rate in the loading‐dose group (RR: 1.44, 95% CI: 1.22–1.69), which remained significant after adjustments for beta‐lactam type, and association between clinical cure and loading dose for clinical cure (RR: 1.47, 95% CI: 1.20–1.80; p = .001). Subgroup analysis of administration type indicated that both groups had low mortality and high clinical cure rates; however, the heterogeneity analysis did not support an association across continuous infusion and extended infusion groups. Subgroup analysis of the Acute Physiology and Chronic Health Evaluation (APACHE) score was conducted; according to APACHE scores ≥ 16, overall mortality and clinical cure significantly differed between CEI and IA. What is new and conclusion CEIs with loading‐dose treatment may significantly improve the clinical outcomes in critically ill sepsis or septic shock patients. Our subgroup and meta‐regression analyses of the loading dose revealed a significantly increased clinical cure rate in the loading‐dose group (RR: 1.44, 95% CI: 1.22–1.69), which remained significant after adjustments for beta‐lactam type, and association between clinical cure and loading dose for clinical cure (RR: 1.47, 95% CI: 1.20–1.80; p = .001). According to APACHE scores ≥ 16, overall mortality and clinical cure significantly differed between CEI and IA.